Leveraging National and Global Political Determinants of Health to Promote Equity in Cancer Care - Dee, Edward Christopher (Archīum Ateneo, 2023)
Health and politics are deeply intertwined. In the context of national and global cancer care delivery, political forces-the political determinants of health-influence every level of the cancer care continuum. We explore the "3-I" framework, which structures the upstream political forces that affect policy choices in the context of actors' interests, ideas, and institutions, to examine how political determinants of health underlie cancer disparities. Borrowing from the work of PA Hall, M-P Pomey, CJ Ho, and other thinkers, interests are the agendas of individuals and groups in power. Ideas represent beliefs or knowledge about what is or what should be. Institutions define the rules of play. We provide examples from around the world: Political interests have helped fuel the establishment of cancer centers in India and have galvanized the 2022 Cancer Moonshot in the United States. The politics of ideas underlie global disparities in cancer clinical trials-that is, in the distribution of epistemic power. Finally, historical institutions have helped perpetuate disparities related to racist and colonialist legacies. Present institutions have also been used to improve access for those in greatest need, as exemplified by the Butaro Cancer Center of Excellence in Rwanda. In providing these global examples, we demonstrate how interests, ideas, and institutions influence access to cancer care across the breadth of the cancer continuum. We argue that these forces can be leveraged to promote cancer care equity nationally and globally.